Evidence-based formulation and overall acceptability of spirulina-enriched functional ice cream. - Bohórquez-Medina, Sofía Lorena; Bohórquez-Medina, Andrea L.; Longa-López, Rosa Alejandra (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: Spirulina, a cyanobacterium recognized for its antioxidant, antiviral, and immunological properties, has been utilized for centuries as a natural source of protein and essential nutrients. Recent studies have highlighted its hypoglycemic and hypolipidemic effects, demonstrating its potential applications in managing non-communicable chronic diseases. However, the distinct flavor of spirulina can lead to low acceptability when incorporated into food products. Objective: This research aimed to review the health benefits of Spirulina platensis and to develop an artisanal spirulina-enriched ice cream formulation that contains no artificial flavoring or coloring additives, in order to evaluate its overall acceptability among trained and untrained panels. Results and discussions: Our findings indicate that the formulation was better received by health and nutrition professionals, while the trained panel reported a higher acceptability for the version containing less spirulina, primarily due to the aftertaste, as it is not a common ingredient. Conclusion: New formulations with stronger flavors may be necessary to mask the aftertaste of spirulina, in order to produce an ice cream with functional properties, given that the spirulina content varies from 1 to 2 grams per serving